Enhancing Employee Performance: The Interplay of Transformational Leadership, Job Satisfaction, and Work Engagement - Eka Kurnia Saputra (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study is driven by the importance of enhancing the performance of civil servants in supporting the effectiveness of public services. Employee performance is influenced by several factors, including transformational leadership, job satisfaction, and work engagement. The aim of this research is to examine the effects of transformational leadership and job satisfaction on employee performance, with work engagement as a mediating variable. The study employs a quantitative approach using a survey method. The research population comprised 4,828 civil servants in the Riau Islands Provincial Government, and a sample of 370 respondents was determined using the Slovin formula. Data were analyzed using Structural Equation Modeling (SEM) based on Smart PLS. The results indicate that job satisfaction and transformational leadership have significant effects on both employee performance and work engagement. Furthermore, work engagement was found to have a significant influence on employee performance and serves as a mediating variable in the relationships between job satisfaction and transformational leadership on employee performance. The findings of this study confirm that enhancing job satisfaction and implementing effective transformational leadership practices can sustainably improve work engagement and civil servant performance.